Synthesis, Characterisation and Application Of Ni/zno/al2o3 Catalyst in Partial Hydrogenation of Sunflower Oil - Wong, Farng Hui (2018)
This work introduced the novelty of incorporating ZnO into Ni/Al2O3 catalyst for application in partial hydrogenation of sunflower oil to enhance activity, reduce trans-fats formation and lower the material cost. Ni/ZnO/Al2O3 catalysts at varying Ni:Zn molar ratios were synthesised by co-precipitation method. They were subsequently characterised and employed in partial hydrogenation to study the effect of ZnO incorporation on the characteristics of Ni/Al2O3 catalyst and its catalytic performance in terms of activity and selectivity. From the study, migration of ZnO to the catalyst surface was observed and the extent of migration decreased with higher ZnO content present in the catalyst. The enrichment of ZnO at the surface was found to alter pore characteristics and resulted in larger pores with diameter up to 27.95 nm. ZnO also functioned as a physical spacer as visualized in the TEM images, which significantly increased the Ni dispersion and Ni surface area but the effect diminished when ZnO became the major constituent. Higher ZnO content in the catalyst was found to suppress trans-fats formation and promote saturated fats formation. Combination of large pore size and high ZnO content in Ni/ZnO/Al2O3 catalyst with Ni:Zn = 1.5:1.5 resulted in improvement of hydrogenation activity by 23 %and reduction of trans-fats formation by 26 % as compared to Ni/Al2O3 catalyst.